1994
DOI: 10.1002/ppul.1950170207
|View full text |Cite
|
Sign up to set email alerts
|

Mucus transport mechanisms in relation to the effect of high frequency chest compression (HFCC) on mucus clearance

Abstract: High frequency chest compression (HFCC) appears promising as a form of chest physiotherapy. Studies published by several clinical centers support its efficacy, and further clinical data are expected to become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 26 publications
1
18
0
2
Order By: Relevance
“…Both regimens were equally safe and effective and it was suggested that the self-applied technique of HFCWO would provide an adequate alternative to conventional physiotherapy. This concurred with a review of the literature published in the same year [37]. KLUFT et al [38] also compared HFCWO with conventional/standard chest physiotherapy and, as more sputum was expectorated during treatment when HFCWO was used, they also concluded that HFCWO was at least as effective.…”
Section: High Frequency Chest Wall Oscillation and Intrapulmonary Persupporting
confidence: 69%
“…Both regimens were equally safe and effective and it was suggested that the self-applied technique of HFCWO would provide an adequate alternative to conventional physiotherapy. This concurred with a review of the literature published in the same year [37]. KLUFT et al [38] also compared HFCWO with conventional/standard chest physiotherapy and, as more sputum was expectorated during treatment when HFCWO was used, they also concluded that HFCWO was at least as effective.…”
Section: High Frequency Chest Wall Oscillation and Intrapulmonary Persupporting
confidence: 69%
“…YFGDO uygulaması sırasında artan hava akışı-mukus etkileşiminin mukus viskoelastisitesini azaltması, ekspiratuar hava akışı sağlaması ve siliyer aktivitenin arttırılması havayolu temizliğini sağlayan fizyolojik mekanizmalardır (20,21). YFGDO aletleri, hava atımlarını sinüzoidal veya triangular dalga formlarıyla meydana getirirler (22,23).…”
Section: Discussionunclassified
“…High frequency chest wall oscillation (HFCWO) causes air to move into and out of the lungs at high velocity but short duration [33]. The high flow of air shears mucus from airway walls, decreases the viscoelasticity of mucus, and promotes cephalad movement of secretions.…”
Section: Mucus Mobilization Devicesmentioning
confidence: 99%